América: Identidad, Integración e Independencia (2013)
The name which has been given to the continent through five centuries of historical miscegenation has marked dependence and integration levels. In the centuries of domination of Spain it was emphasized to call it “New Orb” and “New World”, to diYerentiate it from the old. They were above all names which were imposed. In the same historical synchronicity it was given the name of “Indias” which marked a deep discrimination of the continent as well of  all its inhabitants, including the same Spaniards who upon returning to their native peninsula were referred to, in a derogatory manner, as “Indianos “. The name “America”, originated in a mistake, as well as a profound injustice with Admiral Columbus. However, the men of independence will proudly restore it and its inhabitants will call themselves “Americans” or “American creoles” giving meaning to the origin of a historical identity of “Great Motherland”. In this respect, the ideals of Simon Bolivar, sought to harmonize the identity of America with the independence process and in turn assert the continental integration project. Bolívar’s dream and of the Americans in the early nineteenth century, was aimed at synthesizing these processes in three keywords: identity, independence and integration.